2019
DOI: 10.1002/advs.201900288
|View full text |Cite
|
Sign up to set email alerts
|

Lipidic Aminoglycoside Derivatives: A New Class of Immunomodulators Inducing a Potent Innate Immune Stimulation

Abstract: Development of simple and fully characterized immunomodulatory molecules is an active area of research to enhance current immunotherapies. Monophosphoryl lipid A (MPL), a nontoxic lipidic derivative from bacteria, is the first and currently only adjuvant approved in humans. However, its capacity to induce a potent response against weak immunogenic tumoral‐associated antigens remains limited. Herein, a new generation of lipidic immunomodulators to conduct a structure–activity relationship study to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Pretreatment of Neuro-2a cells with amiloride led to at least 50% reduction in cellular uptake of Au 13 @PDA 5 @PEG 1000 NPs under serum-free and serum-containing conditions (Figure S15). This observation indicates macropinocytosis as a major uptake pathway, in agreement with literature precedent. , [We verified by confocal imaging that amiloride pretreatment effectively blocked the cellular uptake of 70 kDa tetramethylrhodamine (TRITC)-labeled dextran, a common tracer of macropinocytosis, , as evidenced by significant reduction in intracellular TRITC fluorescence (Figure S16). ] Inhibition of energy-dependent endocytosis and actin by pretreatment with sodium azide and cytochalasin D significantly reduced NP uptake, but pretreatment with chlorpromazine and methyl beta-cyclodextrin did not.…”
Section: Resultssupporting
confidence: 89%
“…Pretreatment of Neuro-2a cells with amiloride led to at least 50% reduction in cellular uptake of Au 13 @PDA 5 @PEG 1000 NPs under serum-free and serum-containing conditions (Figure S15). This observation indicates macropinocytosis as a major uptake pathway, in agreement with literature precedent. , [We verified by confocal imaging that amiloride pretreatment effectively blocked the cellular uptake of 70 kDa tetramethylrhodamine (TRITC)-labeled dextran, a common tracer of macropinocytosis, , as evidenced by significant reduction in intracellular TRITC fluorescence (Figure S16). ] Inhibition of energy-dependent endocytosis and actin by pretreatment with sodium azide and cytochalasin D significantly reduced NP uptake, but pretreatment with chlorpromazine and methyl beta-cyclodextrin did not.…”
Section: Resultssupporting
confidence: 89%
“…Moving forward, innovative biomaterials such as O 2 ‐cryogels hold great potential to advance the future of cancer immunotherapy such as T cell‐based immunotherapies (e.g., CAR T cells). [ 50,51,86,87,89–91 ] Considering the clinical approval of several immune checkpoint inhibitors for cancer treatment [ 92 ] and the recent advances in targeting the hypoxia‐adenosinergic signaling pathway, [ 93 ] the combination of O 2 ‐cryogels with immune checkpoint blockade (e.g., CTLA‐4 or PD‐1) [ 17 ] should be investigated for a synergistic effect and improve these treatments. This is further supported with recent studies suggesting hypoxia as a potential obstacle on immune checkpoint inhibitors to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Through the amidation reaction, a family of lipidated aminoglycosides bearing dioleyl, distearyl, dipalmityl, dimyristyl, and cholesterol were prepared. [ 24,25 ] Besides, the aminoglycosides can also be used as monomers to synthesize hyperbranched polymers via Michael‐addition reactions [ 26 ] of the primary amine groups. [ 27,28 ] The amino groups could also perform ring opening reactions with epoxides, [ 29,30 ] affording various lipid‐modified aminoglycosides and hyperbranched aminoglycosides.…”
Section: Aminoglycosides As Building Blocks To Design Functional Biomaterialsmentioning
confidence: 99%
“…It was observed that the vesicles assembled from DOSK with a short spacer (succinyl) and a long unsaturated hydrophobic segment (dioleyl) could trigger a relative stronger upregulation of cell immunity via a caveolae‐mediated endocytosis. [ 24 ]…”
Section: Aminoglycoside‐based Biomaterialsmentioning
confidence: 99%